Directed flow of antiprotons in Au+Au collisions at AGS - Barrette, Jean; Braun-Munzinger, Peter; Esumi, ShinIchi; Filimonov, Kirill; Herrmann, Norbert; Stachel, Johanna; Wessels, Johannes P. (Physics letters, 2000)
Directed flow of antiprotons is studied in Au+Au collisions at a beam momentum of 11.5A GeV/c. It is shown that antiproton directed flow is anti-correlated to proton flow. The measured transverse momentum dependence of the antiproton flow is compared with predictions of the RQMD event generator.